Linguopetic Peculiarities of Repetition in English and Uzbek Folk Epics - Doctoral student Askarova Sh. K. (Zien Journals, 2022)
In this article, in the analysis of the linguistic and cultural aspects of Uzbek and English proverbs, we describe the interdependence of language and culture, consider the thematic similarities of Uzbek and English proverbs, and the expression of mentality and national character in them. we will try to take a deeper approach to such issues.
Keywords: Proverbs; linguistic and cultural; theory; research